How to Drink Like a Mobster : Prohibition-Style Cocktails - Schmid, Albert W. A. (Book collections on Project MUSE., 2018)
Mixology expert Albert W. A. Schmid shows how you can recreate the allure of the gangster bar life with step-by-step instructions on how to set up the best Prohibition-style bar and pour the drinks to match. --Publisher